Social network analysis of murder cases in Indonesian police institutions: Digital public opinion mapping - Puji Santoso (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
This study analyzes the communication behavior of social media users X in responding to a shooting case by a high-ranking Indonesian police official. This study was motivated by the high public response to the murder case of Brigadier Nofriansyah Yosua Hutabarat by Inspector General Ferdy Sambo, which triggered a crisis of trust in the National Police. With a qualitative approach and analysis methods of communication networks and content, data was collected from 18,000 tweets, which included original tweets, retweets, mentions, and comments from within and outside the country. The data is then analyzed using NVivo software for coding and classification. The results of the study show that social media X plays a role as a digital public space where netizens express emotions, form opinions, and create social pressure on state institutions. The structure of communication networks reveals the key actors that shape the public narrative. These findings confirm the importance of social media in the study of public communication and the crisis of institutional legitimacy.